THE INFLUENCE OF LIFESTYLE, FINANCIAL LITERACY, AND SPIRITUAL INTELLIGENCE ON FINANCIAL MANAGEMENT BEHAVIOR WITH LOCUS OF CONTROL AS AN INTERVENING VARIABLE - Siregar, Sarah Veronica; Fadli, Jul Aidil (SULTANIST: Jurnal Manajemen dan Keuangan, 2025)
This study aims to examine the influence of lifestyle, financial literacy, and spiritual intelligence on financial management behavior, with locus of control as a mediating variable, among Micro, Small, and Medium Enterprises (MSME) owners in the Jakarta area. A quantitative approach was employed, with data collected through questionnaires distributed to 200 MSME owners between May and July 2025. The data were analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS 4 software. The results indicate that lifestyle, financial literacy, and spiritual intelligence have a significant effect on financial management behavior, both directly and indirectly through locus of control. Locus of control was found to mediate the relationship between the independent variables and financial management behavior. These findings provide both theoretical and practical contributions, particularly in developing effective financial behavior strategies for MSME owners.